MINI SEMINAR KESEHATAN REPRODUKSI “KUPAS TUNTAS MASALAH ANEMIA, DISMENOREA, SADARI & STRATEGI PENANGANAN DARI PRESPEKTIF KEBIDANAN” - Siskana Dewi Rosita; Wigunantiningsih, Ana; Fakhidah, Luluk Nur (Abdi Geomedisains, 2024)
It is important in the phase of teenagers to get specials attention since in this period the teens experience a lot of change both physically and psychologically even health problems which are often experienced by female teenagers, such as anemia, a lump in the breast and dysmenorrhea which happen every month. However, the teens are still lack of knowledge about reproductive health problems and how to deal with. Even, the female teenagers consider those problems as a common thing and it is considered as something taboo to share. Some teens also feel ashamed to come and check-up at a health center. This community service is wrapped in reproductive health mini-seminar activities to make it more interesting. The methods used during the health education are lecturing, question and answer, and practice. This community service is aimed at improving the teens’ knowledge about anemia, handling dysmenorrhea, and practicing self-awareness (SADARI) independently. This activity was conducted on June 20th, 2019 and followed by 85 students of Muhammadiyah Senior High School 1 from class X and XI. After joining this activity, it is expected that the participants can appropriately react and be responsive to reproductive health problems that are often experienced by teens.